2021
DOI: 10.1002/bse.2782
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development in the craft brewing industry: A case study of Iowa brewers

Abstract: The rapid expansion of the resource‐intensive brewing industry has led to U.S. and state‐level initiatives to encourage sustainable craft brewing practices. These efforts raise questions about brewers' current brewing practices and the conditions and factors that might influence a brewer's decision to adopt sustainable practices. We conducted an in‐depth survey of Iowa craft brewers in 2019 to evaluate current sustainability practices within breweries. In addition, we elicited brewer perceptions regarding cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Rosburg and Grebitus (2021), analyzing a set of breweries in Iowa (USA), concluded that about half of their sample made the annual assessment to evaluate operating procedures and opportunities to improve the environmental practices were identified. In turn, Corsini et al’s (2019) results showed a great need for environmental pro-activeness with CB producers joining forces for more sustainable production, investigating determinants of an environmental strategy.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosburg and Grebitus (2021), analyzing a set of breweries in Iowa (USA), concluded that about half of their sample made the annual assessment to evaluate operating procedures and opportunities to improve the environmental practices were identified. In turn, Corsini et al’s (2019) results showed a great need for environmental pro-activeness with CB producers joining forces for more sustainable production, investigating determinants of an environmental strategy.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Alfeo et al (2020) found that producers intend to give a strong local value added to their production through using small batches of local ingredients, aiming to analyze the cost-benefit relation of Sicilian micro-malting, reaching positive results. Rosburg and Grebitus (2021), analyzing a set of breweries in Iowa (USA), concluded that about half of their sample made the annual assessment to evaluate operating procedures and opportunities to improve the environmental practices were identified. In turn, Corsini et al's (2019) results showed a great need for environmental pro-activeness with CB producers joining forces for more sustainable production, investigating determinants of an environmental strategy.…”
Section: Sustainability (N = 12)mentioning
confidence: 99%
“…Lack of awareness and information about best practices and available state and federal incentives for reducing environmental impacts is a common barrier for craft breweries in any country [75,76]. Brewers guilds, the national Brewers Association, and state programs have been working to address this challenge by providing up-to-date information, technical assistance, and resources such as examples of best practices [15,[82][83][84]. Lack of technical capacity in identifying and carrying out complex energy efficiency or water efficiency projects, analyzing performance data, or evaluating alternatives, is another key barrier to adopting sustainable beer production practices [45].…”
Section: Barriers To Adopting Environmental Initiatives By the Craft ...mentioning
confidence: 99%
“…In Massachusetts, the number of craft breweries increased from 34 in 2007 to over 230 in 2022 [13]. The industry is very committed to environmental and social responsibility, with many small entrepreneurial players focused on local sourcing, reducing energy, water, and chemical use, preventing waste, and promoting social justice and community well-being [14,15]. At the same time, beer manufacturing is water-and energyintensive, generating a significant amount of waste (both liquid and solid) and uses toxic chemicals for cleaning and sterilizing.…”
Section: Introductionmentioning
confidence: 99%
“…Craft breweries are independent, they have limited production volumes with higher differentiation capacity. They attract consumers who demand products more committed to sustainability issues and who are willing to pay higher prices for goods in line with their philosophy of life (Durán-Sánchez et al, 2022;Rosburg and Grebitus, 2021). According to data from the American Brewers Association there has been an increase in the number of microbreweries in Europe and United States (Murray and O'Neill, 2012), which had 3,000 microbreweries in 2014 (Matthews and Patton, 2016).…”
Section: Introductionmentioning
confidence: 99%